Effect of holding time on strain relaxation in high-strength low-alloy steel welds: An in-situ neutron diffraction approach. (January 2022) - Alipooramirabad, Houman; Paradowska, Anna; Reid, Mark; Ghomashchi, Reza
Abstract: In-situ neutron diffraction was employed in the present investigation to study the effects of holding time on the relaxation of residual strains during Post-Weld Heat Treatment (PWHT) for multi-pass High-Strength Low-Alloy (HSLA) steel welds. Different holding time intervals (0.5, 1 and 3 h) were utilized to evaluate and monitor the residual strain relaxation during PWHT. It was found that the holding time has little effects on the strain relaxations as strain relaxations occurs predominantly during the reheating stage of the heat treatment ( 80% of strain relaxation). A similar trend is observed for all three holding time arrangements with the high strain relaxation during the reheating stage followed by linear strain relief may confirm the hypothesis that creep (primary and secondary) is responsible for strain relaxation during PWHT. It further confirms the selected soaking temperature of 600 °C has a significant effect on the stress relaxation. This finding is in line with the microstructural characterization studies indicating the formation of sub-grains through polygonization in the Heat Affected Zone (HAZ) and Weld Metal (WM) of the heat treated joints. Ex-situ neutron diffraction which was conducted after PWHT confirmed the in-situ neutron diffraction results and showed slightly higher level of residual stresses for the heat-treated specimen with 1/2 hour holding time ( 32% of yield strength of the WM). Furthermore, the tensile, hardness and Charpy impact test results support the notion that a shorter holding time is more beneficial, not only for the cost issues but also for the microstructural and mechanical properties of the welded joints. The findings of this study can be used to optimize the current PWHT codes and standards. It can also be used for the validation studies of the finite element modeling of this process.